Exploring the potential role of citizen science in the warning value chain for high impact weather - Tan, Marion Lara; Hoffmann, David; Ebert, Elizabeth; Cui, Alicia; Johnston, David (Frontiers in Communication, 2022)
Preparing and delivering warnings to the public involves a chain of processes spanning different organizations and stakeholders from numerous disciplines. At each stage of this warning chain, relevant groups apply their expertise, but sharing information and transmission of data between groups is often imperfect. In diverse research fields, citizen science has been valuable in filling gaps through contributing local data. However, there is limited understanding of citizen science’s role in bridging gaps in the warning value chain. Citizen science research projects could help improve the various aspects of the warning value chain by providing observations and evaluation, data verification and quality control, engagement and education on warnings, and improvement of accessibility for warnings. This paper explores the research question: How can citizen science contribute to the warning value chain? Two workshops were held with 29 experts on citizen science and the warning value chain to answer this question from a high impact weather perspective. The results from this study have shown that citizens, at individual or collective capacity, interact throughout the chain, and there are many prospects for citizen science projects for observations, weather, hazard, and impact forecasting, to warning communication and decision making. The study also revealed that data quality control is a main challenge for citizen science. Despite having limitations, the findings have shown that citizen science can be a platform for increasing awareness and creating a sense of community that adds value and helps bridge gaps in the warning value chain.